2009
DOI: 10.1007/s11661-009-9845-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinking Nonlinear Elasticity and the Deformation of Magnesium

Abstract: Despite a large body of work devoted to understanding the deformation of polycrystalline magnesium, there are still some outstanding questions, not the least of which are the nature of its microyielding and the nature of its fully reversible, hysteretic, stress-strain curves. In this article, we provide further evidence that Mg is a kinking nonlinear solid by showing excellent agreement between the predictions of our microscale model, in which fully reversible, dislocation-based incipient kink bands (IKBs) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 65 publications
4
37
0
Order By: Relevance
“…If one assumes, w = b, then s loc % G/30, and c c is of the order of 0.05 rad. If, as assumed here and in our previous work [4][5][6][7], w = 5b, then c c = 0.012 rad.…”
Section: Dislocation Densitiesmentioning
confidence: 69%
See 2 more Smart Citations
“…If one assumes, w = b, then s loc % G/30, and c c is of the order of 0.05 rad. If, as assumed here and in our previous work [4][5][6][7], w = 5b, then c c = 0.012 rad.…”
Section: Dislocation Densitiesmentioning
confidence: 69%
“…As noted above, due to their high c/a ratios (3)(4)(5)(6)(7)(8), neither non-basal dislocations nor twins have ever been implicated in the deformation of the MAX phases under normal loading conditions. Referring to insets (i) and (ii) in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A breakthrough toward understanding the early deformation of HM came about recently when we showed that they are kinking nonlinear elastic, KNE, solids. [1][2][3] Macroscopically, KNE solids are characterized by the formation of fully, and spontaneously, reversible closed hysteresis stress-strain loops. The size of these loops, which corresponds to the energy dissipated per unit volume, scales with the maximum applied stress squared and is a strong function of grain size.…”
Section: Introductionmentioning
confidence: 99%
“…Kinking is generally known as a minor deformation mode in crystalline materials, 15) but it appears to be an essential mode for the LPSO crystals, for which both the non-basal slip and twinning are strongly suppressed. Typical microstructures of the kink-deformation bands in the LPSO phase grains were shown to be represented by straight boundaries, across which the host crystals are sharply bended with rotational angles from 10 to 90 degrees.…”
Section: Introductionmentioning
confidence: 99%